Pathway Commons 2019 Update: integration, analysis and exploration of pathway data. Issue Volume 48:Issue D1(2020) (24th October 2019) - Rodchenkov, Igor; Babur, Ozgun; Luna, Augustin; Aksoy, Bulent Arman; Wong, Jeffrey V; Fong, Dylan; Franz, Max; Siper, Metin Can; Cheung, Manfred; Wrana, Michael; Mistry, Harsh; Mosier, Logan; et al.
Abstract: Pathway Commons (https://www.pathwaycommons.org ) is an integrated resource of publicly available information about biological pathways including biochemical reactions, assembly of biomolecular complexes, transport and catalysis events and physical interactions involving proteins, DNA, RNA, and small molecules (e.g. metabolites and drug compounds). Data is collected from multiple providers in standard formats, including the Biological Pathway Exchange (BioPAX) language and the Proteomics Standards Initiative Molecular Interactions format, and then integrated. Pathway Commons provides biologists with (i) tools to search this comprehensive resource, (ii) a download site offering integrated bulk sets of pathway data (e.g. tables of interactions and gene sets), (iii) reusable software libraries for working with pathway information in several programming languages (Java, R, Python and Javascript) and (iv) a web service for programmatically querying the entire dataset. Visualization of pathways is supported using the Systems Biological Graphical Notation (SBGN). Pathway Commons currently contains data from 22 databases with 4794 detailed human biochemical processes (i.e. pathways) and ∼2.3 million interactions. To enhance the usability of this large resource for end-users, we develop and maintain interactive web applications and training materials that enable pathway exploration and advanced analysis.